In Situ Electrochemical Investigations of Inherently Chiral 2, 2′‐Biindole Architectures with Oligothiophene Terminals. Issue 17 (22nd June 2021) - Malacrida, Claudia; Scapinello, Luca; Cirilli, Roberto; Grecchi, Sara; Penoni, Andrea; Benincori, Tiziana; Ludwigs, Sabine
Abstract: The synthesis and characterization of three new inherently chiral N, N′ ‐dipropyl‐3, 3′‐diheteroaryl‐2, 2′‐biindole monomers, nicknamed Ind2 T4, Ind2 T6 and Ind2 Ph2 T4, which differ in the number of thiophenes as terminals, are reported. In addition to a full monomer characterization, stable electroactive oligomeric films were obtained by electro‐oxidation upon cycling to potentials which activate the thiophene terminals. Cyclic voltammetry, UV‐Vis‐NIR spectroelectrochemistry and in situ conductance measurements show that oligomeric films of Ind2 T6 present the best stability and electrochromic switching performance. Enantioselective tests with a chiral ferrocene amine clearly show the potential as chiral selectors for analytical and sensing purposes. Abstract : Chiral organic electroactive layers are increasingly gaining interest due to their outstanding stereoselective sensing performance. This article presents the synthesis of three new inherently chiral 3, 3′‐diheteroaryl‐2, 2′‐biindole monomers, nicknamed Ind2 T4, Ind2 T6, and Ind2 Ph2 T4, and the complete electrochemical characterization of their oligomerized films. A fully reversible electrochromic behavior of all the films is observed, with oligo−Ind2 T6 layers presenting the best stability and switching performance. Oligo−Ind2 T6 films also show a remarkable enantioselective response towards both optical antipodes of a ferrocenyl−amine chiral probe.